Association between workload of the nursing staff and patient safety outcomes - Ana Maria Müller de Magalhães; Diovane Ghignatti da Costa; Caren de Oliveira Riboldi; Thiane Mergen; Amanda da Silveira Barbosa; Gisela Maria Schebella Souto de Moura (Revista da Escola de Enfermagem da USP, 2017)
Abstract OBJECTIVE To describe the workload of the nursing team and relate it with patient safety outcomes in clinical and surgical inpatient units of a university hospital. METHOD Cross-sectional study, carried out from October 2013 to September 2015. The factor under study was the workload, expressed as the ratio between the mean number of patients and the number of nursing professionals in 24 hours and in the day shifts. RESULTS The sample consisted of 157,481 patients, 502 nursing professionals and 264 observations of safety outcomes. The ratios of patients per nurse and per nursing technician in day shifts indicate a mean estimate of 14-15 and 5-6 patients per professional, respectively. There was a significant association between the workloads in the inpatient units and average length of stay, urinary infection related to invasive procedure and the satisfaction of patients with nursing care. CONCLUSION The increase in the workload of the nursing team had an impact on quality of care and safety for patients. An adequate staffing promotes a safer care environment.